Determining the Impact of Urbanization on Green Spaces Using NDVI Analysis: The Case of Konya City - Taha Kagan Aydin (The Eurasia Proceedings of Health, Environment and Life Sciences, 2026)
Rapid population growth and urbanization processes lead to significant changes in land use/cover, particularly in developing cities, often resulting in the reduction of green spaces. In this study, the impact of urbanization on vegetation Dynamics in Konya, located in the Central Anatolia Region of Türkiye, was analyzed using the Normalized Difference Vegetation Index (NDVI). Landsat satellite images from 2015 and 2025 were utilized to reveal the temporal and spatial variations in vegetation density. The analysis of NDVI values indicates that vegetation cover has notably decreased, particularly in areas experiencing urban expansion. Considering the development pattern of Konya over the last decade, it is evident that urban growth has predominantly occurred over agricultural lands and natural vegetation areas, leading to an overall declining trend in NDVI values. However, localized increases in NDVI were also observed in green spaces such as parks and recreational areas. This finding suggests that urbanization does not produce exclusively negative impacts; rather, its effects are strongly dependent on the nature of urban development and planning approaches. In conclusion, the case of Konya demonstrates that urbanization generally leads to a reduction in vegetation density. NDVI based analyses prove to be an effective tool for evaluating the ecological impacts of urban growth. The integration of such analyses into sustainable urban planning processes contributes to the protection and enhancement of green spaces and supports the development of scientifically informed strategies aimed at mitigating ecological impacts.